Faktor Faktor yang Mempengaruhi Minat Belajar Siswa Mengikuti Pembelajaran Tatap Muka Masa Pandemi Covid-19 Pada Mata Pelajaran Ekonomi di SMA 2 Gunung Talang - Dessyta Gumanti; Reni Respita; Salman M Noer (Universitas Negeri Surabaya, 2023)
Face-to-face learning has been carried out again after during the covid-19 pandemic learning was carried out online and face-to-face was limited. The purpose of this study is the influence of the school environment, learning readiness and parental attention on students' learning interest in economic subjects in face-to-face learning during the Covid-19 Pandemic Period at SMAN 2 Gunung Talang. The type of research is associative descriptive research. The population in this study were all students of SMAN 2 Gunung Talang with Proportional Random Sampling sampling technique obtained as many as 81 students. The instrument used is a closed questionnaire using the t test and F test. Data analysis uses multiple regression analysis where the results of the study are obtained partially for each variable, namely the school environment, learning readiness, and parental attention have a positive and significant effect on students' interest in learning to take part in face-to-face learning during the Covid-19 Pandemic Period on economic subjects in SMAN 2 Gunung Talang. Taken together, there is a significant influence between the school environment, learning readiness and parents' attention to students' interest in learning to take part in face-to-face learning during the Covid-19 Pandemic Period on economic subjects at SMAN 2 Gunung Talang.